2009
DOI: 10.1080/08820130902874110
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses of the Effects of Drugs of Abuse on Monocyte-Derived Mature Dendritic Cells

Abstract: Drug abuse has become a global health concern. Understanding how drug abuse modulates the immune system and how the immune system responds to pathogens associated with drug abuse, such hepatitis C virus (HCV) and human immunodeficiency virus (HIV-1), can be assessed by an integrated approach comparing proteomic analyses and quantitation of gene expression. Twodimensional (2D) difference gel electrophoresis was used to determine the molecular mechanisms underlying the proteomic changes that alter normal biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Moreover, recent studies have determined that cocaine enhances HIV-1 induced CD4+ T cell apoptosis and contributes to disease progression among drug users (Pandhare et al 2014). Proteomics analyses of monocyte-derived mature dendritic cells demonstrated the effects of cocaine in enhancing HIV-replication with over-expression of important proteins such as aldolase, enolase, cathepsin S, HSP90, MEK1, MEK2 among others (Reynolds et al 2009). Studies in human astrocytes exposed to cocaine also demonstrated that increased enolase, aldolase, HSP60, Anexin I among others (Reynolds et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have determined that cocaine enhances HIV-1 induced CD4+ T cell apoptosis and contributes to disease progression among drug users (Pandhare et al 2014). Proteomics analyses of monocyte-derived mature dendritic cells demonstrated the effects of cocaine in enhancing HIV-replication with over-expression of important proteins such as aldolase, enolase, cathepsin S, HSP90, MEK1, MEK2 among others (Reynolds et al 2009). Studies in human astrocytes exposed to cocaine also demonstrated that increased enolase, aldolase, HSP60, Anexin I among others (Reynolds et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 directly affects dendritic cells (DC) and leads to dysfunction of immune system manifested by increased levels of inflammatory cytokines, chemokines and neurotoxin such as quinolinic acid and arachidonic acid (AA) [9], [10]. Increasing evidence suggests that DCs play a major role in the defense against HIV infection and illicit drug such as cocaine [11][13]. Immature dendritic cells (IDC) specialize in capturing and processing antigens and plays wide role in cell maturation, migration to CD4+ T cells, and T cell activation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent evaluation and selection by several quality criteria (see Materials and Methods) led to identification of 194 peptides derived from 64 different proteins (Supplementary Table 1, only online). Proteomic profiling of human monocyte-derived dendritic cells revealed that a number of these peptides are derived from ubiquitously expressed proteins (e.g., from house-keeping, cytoskeletal, or matrix proteins) 34,35,36,37,38,39,40,41,42,43. These include ribosomal proteins, actin and actin-related proteins, aldolase A, annexin A2, β2-micoglobulin, calmodulin, cathepsin proteins, superoxide dismutase, systatins, elonase 1, galectin 1, glycolysis-related enzymes, histones, HSP70, IL-1RA, kynureninase, macrophage migrating inhibitory factor, peroxiredoxin 6, phosphoglycerated kinase 1, S100 calcium binding proteins and vimentin.…”
Section: Resultsmentioning
confidence: 99%